Legal Protection for Consumers Against Fake Reviews on E-Commerce Platforms: The Perspective of Consumer Protection Laws - Suharto; Ali Huristak Hartawan Hasibuan; Yanuriansyah Ar Rasyid (Jurnal Ilmu Hukum Kyadiren, 2026)
This study aims to analyze regulations related to fake reviews on e-commerce platforms based on consumer protection laws, examine platform policies in preventing fake reviews, and identify obstacles to law enforcement. The method used is normative juridical with a statutory and conceptual approach, using secondary, primary, and tertiary data that are analyzed qualitatively descriptively. The results of the study show that the regulation of fake reviews has been covered in the UUPK and the ITE Law, although it is not explicitly mentioned. Platforms such as Shopee, Tokopedia, and Lazada have prevention policies, but law enforcement is constrained by the burden of proof and low consumer reporting. It is recommended that the government and e-commerce platforms develop automatic detection technology and make it easier for consumers to return goods.